The application of ketamine in pain management for sports injuries and other medical conditions - literature review - Nowicka, Katarzyna; Klimek, Wiktor; Ignatiuk-Chilkiewicz, Marta; Olszańska, Monika; Hakało, Dominika; Kałuska, Joanna; Suprun, Tomasz; Sokół, Aleksandra; Mościszko, Klaudia; Majewska, Maria (Quality in Sport, 2025)
Introduction: Ketamine is a well-established dissociative anesthetic. The discovery of its NMDA receptor antagonism revealed new potential applications in pain management. It has demonstrated promise as an analgesic for the treatment of chronic pain and has proven useful in managing acute pain, such as that resulting from sports injuries or in pediatric care settings. It is also a valuable alternative for patients who have not responded well to traditional pain medications. Materials and methods: This article reviews promising role of ketamine in pain management, especially in chronic or cancer pain, incorporating data from Google Scholar, PubMed, using keywords such as „ketamine”,„chronic pain”, „acute pain”, „pain management”. Summary: Current evidence supports the use of subanesthetic ketamine as an effective option for acute pain management across various clinical settings, with potential to reduce opioid dependence. Its unique antidepressant properties also make it beneficial for chronic pain patients, especially those with comorbid depression. In conditions like CRPS and sickle cell disease, low-dose ketamine has shown promising results in improving pain and function. However, its effectiveness in fibromyalgia appears limited, with short-term infusions offering only temporary relief. The pediatric population may particularly benefit from ketamine’s rapid, intranasal administration, though dosing and safety must be carefully considered. While early findings are encouraging, more research is needed to establish optimal protocols and to explore its role in managing sport-related injuries. Conclusions: Ketamine finds various applications in pain therapy and is a promising medication due to its efficacy in both chronic and acute pain management. However, further research is necessary to precisely determine the therapeutic dosage ranges, the long-term effects of its use, and the risk of addiction associated with its administration.